PROBLEMATIKA BIMBINGAN BADAN PENASEHATAN PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) BAGI CALON PENGANTIN - Sri Dianti; Patriana (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
ABSTRACT Marriage advice or usually referred to as BP4 is part of a series marriages that is usually conveyed by the “PENGHULU” to the bride and groom as provisions in undergoing the household ark. Judging from its role, marriage advice is very important and necessary for groom to understand how to live a married life and lead a SAKINAH, MAWADDAH and WARRAHMAH family. Seeing the importance of the role of BP4, then the implementation process must be well regulated, the time and place and the material must be adjusted to the participants, so that the “CANTIN” can absorb the knowledge of marriage that is conveyed. However, what happens in the field is that the implementation of BP4 is sometimes not scheduled and only takes a little time. This usually happens in several areas of the Sambas Regency. This is very influential on the prospective bride and groom who only consider the implementation of marriage advice only as a formality and do not take the material presented seriously. So that many newlywed couples easily decide on divorce without thinking long. It could be that one of the contributing factors is the problems in the implementation of BP4 which makes marriage advice not conveyed and well received by the bride and groom.